MULTILINGUALISM AND ACADEMIC ACHIEVEMENT: MYTHS VS. REALITY - Nosirova Umidaxon Ikromovna; Maxamadjonova Nodiraxon Axmadiyor qizi (Modern American Journals, 2025)
In the last century, multilingualism has become both a social and educational reality shaped by globalization, migration, and increasing intercultural communication. The ability to speak and learn in multiple languages is no longer limited to specific regions but has become a defining characteristic of modern societies and education systems worldwide. Despite its growing importance, myths and misunderstandings about the effects of multilingualism on learning continue to persist. Some educators and parents still fear that learning several languages simultaneously may confuse students, slow their linguistic development, or hinder academic performance in other subjects. Others, however, argue that multilingualism offers powerful cognitive and social benefits, fostering creativity, mental flexibility, and enhanced communication skills. This article investigates the complex relationship between multilingualism and academic achievement through a review of both international and Uzbek research. The findings indicate that multilingualism contributes positively to educational success by enhancing literacy, problem-solving skills, and academic performance. It also promotes intercultural competence and adaptability — skills which are essential for thriving in a globalized world. However, challenges remain, such as language interference, unequal access to quality instruction in all languages, and the undervaluation of minority languages in formal education. Addressing these issues requires well-designed language policies and mother-tongue-based multilingual education programs that respect linguistic diversity while ensuring equal learning opportunities. Evidence from both global and local contexts confirms that when students first learn in their mother tongue and gradually acquire additional languages, their comprehension, confidence, and long-term academic outcomes are significantly strengthened. Therefore, multilingualism should not be viewed as an obstacle but as an educational resource that enriches intellectual growth and supports inclusive, high-quality education for all learners.
Keywords: Monolingual, Bilingual, Multilingual, Academic success, Cognitive ability, Mother-tongue-based education.